Women's Body Image Throughout the Adult Life Span: A Latent Growth Modeling Approach. (October 2020) - Lee, Minsun; Damhorst, Mary Lynn
This retrospective study examined developmental trajectories of women's body image perceptions throughout the adult life span from life course and self-discrepancy theory perspectives. Data were collected from women over 65 years of age, recruited from 15 senior communities and centers in a Midwest U.S. state in 2012. A total of 102 older women completed a survey about their past and current body image perceptions. To examine developmental trajectories of the repeated body image measures, a latent growth modeling analysis was adopted. Distinct and significant trajectories in each body image measure during the entire adult life course were found, confirming that a retrospective account of women's body image perceptions significantly change with age. The individual differences in the trajectories over time and the relationship between an individual's initial mean level and the rate of change on each variable were also examined. The findings advanced understanding of the retrospective age effects on women's body image throughout the adult life span.